Implementation Trauma Healing Through Cognitive Behavioral Therapy to Overcome Anxiety in Women of Reproductive Age After Landslide Disasters - Herlina Evi Yanti Manik; Jojor Silaban; Verawaty Fitrinelda Silaban (Indonesian Journal of Global Health Research, 2026)
Indonesia is a disaster-prone country located on the Ring of Fire and frequently experiences hydrometeorological disasters, including landslides. Landslides not only cause physical and economic losses but also lead to psychological impacts, particularly anxiety, which is most often experienced by vulnerable groups such as women of childbearing age (WUS). Anxiety after disasters, if left untreated, can disrupt daily functioning and reduce quality of life. Cognitive Behavioral Therapy (CBT) has been recognized as an effective intervention to reduce anxiety and improve psychological resilience. This study aimed to analyze the level of anxiety in women of childbearing age after a landslide disaster and to evaluate the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing anxiety. This quantitative study used an experimental pretest-posttest control group design. The population consisted of 40 women. The sample is a part of the accessible population that will be used as the subject of research using sampling techniques. The research sample is 20 people in the experimental group and 20 people in the control group.  Childbearing age in the Lae Parira Health Center area, Dairi Regency, from April to October 2025. Samples were divided into two groups: 20 respondents in the experimental group receiving CBT and 20 respondents in the control group. Data were collected through interviews, observations, and standardized anxiety assessment. analysis using univariate analysis and bivariate analysis. The CBT group showed a significant decrease in anxiety scores from a median of 16 to 7 (Z = −4.76; p < 0.001; r = 1.07), while the control group experienced only a slight reduction from 17 to 15 (Z = −3.49; p < 0.001; r = 0.78). Between-group comparison confirmed that CBT was significantly more effective (Z = 5.41; p < 0.001; r = 0.86). Cognitive Behavioral Therapy is highly effective in reducing anxiety among women of childbearing age after a landslide disaster. Its implementation in primary healthcare settings can support post-disaster psychological recovery and improve community resilience.